Understanding Nigerian e-mail scams: A computational content analysis approach. Issue 2 (4th March 2021) - Genc, Yegin; Kour, Harpreet; Arslan, Hasan T.; Chen, Li-Chiou
ABSTRACT: e-mail scams have been around for a long time, and they are still remarkably successful. Understanding these scams can help combat fraud by raising public awareness and improving anti-fraud technologies. We conducted an in-depth analysis of e-mail contents with a mixed-method approach using machine-learning-based content analysis and qualitative analysis. We identified five stories (i.e., topics) scammers used in their e-mails. Further, we explored similarities between messages from the same scammers. Our findings suggest some scammers resend a message with the same story as before but with highly textual differences. We argue this might be a deceptive maneuver to avoid spam blockers.